Modeling of Inventory Application of Goods Islamic University of Kuantan Singingi: Modeling of Inventory Application of Goods Islamic University of Kuantan Singingi - Febri Haswan (Institute of Computer Science (IOCS), 2020)
Kuantan Singingi Islamic University is located in Riau Province, Kuantan Singingi Regency, where currently inventory data processing has not used an application. Inventory data processing carried out by the BPAUK Section is still done manually so that the data processing becomes ineffective and inefficient. With the application, it can facilitate the BPAUK Section in processing inventory data. The method used in this research is observation, interview, literature, analysis, design or design using UML (Unified Modeling Language) modeling. The results of this study are an inventory data processing application at the Kuantan Singingi Islamic University which is expected to be implemented into the program, so as to increase the effectiveness and efficiency of work.